Effect of Combined Endurance Training and MitoQ on Cardiac Function and Serum Level of Antioxidants, NO, miR-126, and miR-27a in Hypertensive Individuals. (13th January 2022) - Masoumi-Ardakani, Yaser; Najafipour, Hamid; Nasri, Hamid Reza; Aminizadeh, Soheil; Jafari, Shirin; Moflehi, Daruosh
Abstract : Objectives . Hypertension (HTN) is one of the most important risk factors for cardiovascular diseases. Despite advances in treatment and control of HTN, the prevalence of HTN is still increasing. MitoQ is a supplement that acts on mitochondria and attenuates reactive oxygen species (ROS), which plays an important role in cardiovascular health. miRNAs play an important role in the pathophysiology of HTN. We evaluated the effects of MitoQ supplementation and endurance training (ET), alone and in combination, on functional indices of the heart and serum levels of miR-126, miR-27a, antioxidants, and NO, in patients with HTN. Methods . In a double-blind randomized clinical trial, 52 male participants (age 40-55 years) were randomly divided into four groups (n = 13 ) of placebo, MitoQ (20 mg/day, oral), ET (cycle ergometer, moderate intensity, 40-60% VO2 peak, heart rate 120-140 b/min, 45 min a day, three days/week for six weeks), and MitoQ+ET. Cardiac function indices were assessed by echocardiography before and after interventions. Results . Systolic blood pressure (SBP) significantly decreased in all intervention groups (P < 0.001 ) while DBP (P < 0.01 ) and LV hypertrophy (P < 0.05 ) were significantly decreased only in the MitoQ+ET group. Serum levels of SOD, GPx, and NO and the level of miR-126 significantly increased in all treatment groups, while miR-27a reduced in the ET (P < 0.05 ) and MitoQ+ET (P < 0.01 ) groups. Conclusions . Compared to MitoQ and ET alone, their combination has more prominent improving effects on cardiac health and amelioration of BP in the patients with HTN. These effects are through miR-126 and miR-27a modulation and ameliorating mitochondrial ROS production.